A 9–12 GHz 5-bit active LO phase shifter with a new vector sum method. (1st January 2015) - Chen, Changming; Li, Wei; Li, Ning; Ren, Junyan
Abstract This paper presents a 5-bit active LO phase shifter with a new vector sum method for 9–12 GHz applications. The 5-bit phase shifter is composed of four 3-bit sub phase shifters by adopting the new vector sum method, which reduces the requirements on the resolution of the variable gain amplifier (VGA). The variable gain function is realized by switch on/off parallel input transistor pairs rather than changing the bias current of the VGA, which avoids the linearity variation and drain-source voltage variation existing in the quadrature vector sum active phase shifter. The 5-bit active LO phase shifter is fabricated in TSMC 0.13 μm CMOS technology. The measured results show that the phase shifter achieves 5-bit phase shift accuracy. The average conversion gain for 32 phase states is −0.5 to 7 dB from 9 to 12 GHz. The RMS gain error and the RMS phase error are smaller than 0.8 dB and 4° respectively. The current consumption is 27.7 mA from a 1.2 V supply voltage.